Cardiovascular risk of Janus kinase inhibitors compared with biologic disease-modifying antirheumatic drugs in patients with rheumatoid arthritis without underlying cardiovascular diseases: a nationwide cohort study - Song, Yun-Kyoung; Lee, Gaeun; Hwang, Jinseub; Kim, Ji-Won; Kwon, Jin-Won (Frontiers in Pharmacology, 2023)
Objectives: Despite the ethnic differences in cardiovascular (CV) risks and recent increase in the prescription of Janus kinase (JAK) inhibitors, limited evidence is available for their CV outcomes in Asian patients with rheumatoid arthritis (RA). We aimed to compare the major adverse CV events (MACEs) of JAK inhibitors to those of biologic disease-modifying antirheumatic drugs (bDMARDs) in Korean patients with RA without baseline CV disease (CVD). Methods: In a nationwide retrospective cohort study, patients newly diagnosed with RA without a history of CVD between 2013 and 2018 were identified using the National Health Insurance Service database. The cohort was followed up until the end of 2019 for the development of MACEs. Hazard ratios (HRs) for MACEs such as myocardial infarction, stroke, coronary revascularization, or all-cause death, were estimated using Cox proportional hazard regression in a propensity score-matched cohort. Results: In total, 4,230 matched patients with RA were included (846 JAK inhibitor users and 3,384 bDMARD users). The crude incidence rate (95% confidence intervals, CI) per 100 patient-years for MACEs was 0.83 (0.311.81) and 0.74 (0.531.02) in the JAK inhibitor and bDMARD groups, respectively. The risk of MACEs was not significantly different between JAK inhibitor and bDMARD users with an adjusted HR (95% CI) of 1.28 (0.533.11). There were no significant differences in the risk of MACEs between JAK inhibitors and bDMARDs in each subgroup according to the types of bDMARDs, age, sex, Charlson comorbidity index score, and comorbidities. Conclusions: Compared to bDMARDs, JAK inhibitors were not associated with the occurrence of MACEs in Korean patients with RA without a history of CVD.